Impersonal subjectivation from platforms to infrastructures. (March 2019) - Langlois, Ganaele; Elmer, Greg
The rapid expansion of social media has led to the concentration of digitized, networked, and mediated processes into the hands of a few giant corporations (e.g. Google, Facebook, and Amazon), their partners and affiliates. From smart watches to targeted advertising and reputation scores, this new political economy of subjectivation – or subject making – sees an intensification of datafication to sell commodities, manipulate moods, inject ideologies, and influence behaviors. This article argues that in order to understand this new political economy of subjectivation, we need to complicate and build upon framework that focus on the collection of personal data and its risks on individual users. We argue that as social media and digital media giant corporations move away from an enclosed platform model toward a distributed, impersonal infrastructure, the mining of individual data and the shaping of individual attitudes is increasingly geared toward establishing relationships between user data and a plethora of non-human, environmental data. Such an infrastructure invokes impersonal subjects, and thus requires a new politics of relationality.